TRADISI BAJIKEA MASYARAKAT KENEGERIAN BATURIJAL, KECAMATAN PERANAP, KABUPATEN INDRAGIRI HULU - Roswinda Roswinda; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Bajikea is a tradition that is in Kenengerina Baturijal which has developed in the year. This study aims (1) To find out the history of the origin of the Bajikea tradition in Kenegerian Baturijal, Peranap District, Indragiri Hulu Regency, (2) To find out the meaning of the Bajikea tradition in Kenegerian Baturijal, Peranap District, Indragiri Hulu Regency (3) To find out the procedures implementation of the Bajikea tradition in Kenegerian Baturijal, Peranap District, Indragiri Hulu Regency, (4) To find out the perceptions of the young generation towards the preservation of the Bajikea tradition in Kenegerian Baturijal, Peranap District. Indragiri Hulu District, (5) To find out how to preserve the Bajikea tradition in Kenegerian Baturijal, Peranap District, Indragiri Hulu Regency. The results of the research obtained show that Bajikea comes from the word Zikir, which is a prayer, praise and narration of the history of the Prophet Muhammad SAW which is pronounced in a rhythm or tone that is usually performed during the night of the wedding, circumcision and others. This Bajikea is one of the original art traditions of Baturijal. The first procedure for implementing this Bajikea is ninik mamak or tenganai who will perform a celebration coming to the house of the Bajikea chairman. Bajikea is an art performance by singing 3 poems. The first procedure for implementing Bajikea is ninik mamak or tenganai who will perform a celebration coming to the house of the Bajikea chairman named Mr. Wal to ask to be present at the event that will be invited such as: Marriage, Circumcision and others, the younger generation is the next generation, the Bajikea tradition in Baturijal has been preserved for a long time by our elders. social media, taught to the younger generation through desktop-based interactive applications such as flash, visual basic, etc., and also through mobile-based applications, such as Android or iOS, or even game-based applications.Key Words: The Bajikea Tradition of The State Community of Baturijal, Roleap Sub-District,Indragiri Upstream District